The electricity purchasing and selling strategy of load aggregators participating in China’s dual-tier electricity market considering inter-provincial subsidies - Haonan Zhang; Youwen Tian; Xiang Liu; Ming Kuang; Nannan Zhang (Scientific Reports)
Abstract To promote the optimal allocation of electricity resources, this paper designs a trading framework for small and medium-sized adjustable electricity users to participate in China’s dual-tier electricity market through load aggregators, proposes an inter-provincial transaction correction subsidy coefficient, and analyzes the purchase cost and risk at multiple time and space scales. Combining user demand response and preference behavior, a purchase and sale electricity decision-making model is constructed to achieve revenue maximization and risk control. The experimental results show that the spot purchase strategy proposed in this paper faces relatively low market risks. After applying the subsidy, the daily profit of the load aggregator increases by 145%; the inter-provincial purchase volume increases, and the resource allocation is optimized; the electricity charges of terminal users decrease, with a reduction range of 3.08–7.78 $/MWh. This indicates that the participation of small and medium-sized adjustable electricity users’ loads in the dual-tier electricity market through load aggregators expands the trading scope, which is conducive to enhancing the efficiency and sustainable development of the electricity market.